The Effect of Cooperative Integrated Reading and Composition Strategy towards Reading Comprehension at Tenth Grade Students of Vocational High School 1 Muaro Jambi - Yanti Ismiyati; Ridho Praja Dinata (Jurnal Ilmiah Dikdaya, 2023)
The purpose of this research is to find out the effect of Cooperative and Integrated Reading and Composition Strategy toward student reading comprehension at tenth grade students of Vocational High School 1 Muaro Jambi. Th research design in this research was quantitative research design with experimental research approach. The population of this research was tenth grade student and the sample were class XTKJ 1 and XTKJ 2 with simple random technique. The research instrument was test with multiple choice test. The data collection was pre-test, treatment and post-test. The data analysis in this research by using ttest formula. The result of the research was found that the students’ ability in reading comprehension in experimental class got mean score 43,85 in pre-test with the maximum score 55 and the minimum score was 30. While in post-test the students got mean 70,14 with the maximum score 60 and the minimum score 85. Then, in control class the students got mean 46,42 in pre-test with the maximum score 55 and the minimum score was 30. While in post-test the students got mean 76,00 with the maximum score 65 and the minimum score was 55. Based on the statistical computation t–test was found that the coefficient of observation = 2,270, where the coefficient of t-table = 1,995. It means that there was significant effect of using Cooperative Integrated Reading and Composition (CIRC) technique. It was indicated that Ha was accepted and H0 was rejected. In addition, there is effect of using Cooperative Integrated Reading and Composition (CIRC) technique towards student reading comprehension mastery